Determining the Relationship Between Workplace Bullying Perceptions and Professional Commitment Levels Among New Graduate Nurses - Merve Tarhan; Merve Akbudak; Merve Can; Ayşenur Kale (Association of Nurse Managers, 2022)
Aim: This study aimed to determine the relationship between new graduate nurses' perceptions of workplace bullying and their levels of professional commitment. Methods: The descriptive-correlational study was conducted with 126 new graduate nurses between April and May 2021 in a foundation university hospital, İstanbul. Data were gathered using a self-administered questionnaire with three sections: A personal information form, a Workplace Bullying Scale, and a Nursing Professional Commitment Scale. The data were analyzed using descriptive tests, the Mann-Whitney U test, the Kruskal-Wallis H analysis of variance, and the Spearman correlation analysis. Results: Workplace bullying perceptions and professional commitment levels among new graduate nurses were moderate, with median scores of 54.5 (42-65) and 63 (58-72), respectively. New university graduates who were rarely supported by their managers (p<.001), often bullied (p<.01), and often did not want to go to work (p<.001) were significantly more likely to perceive workplace bullying. A weak, negative correlation was found between perceptions of workplace bullying and level of job engagement (rs=-.32; p<.001). Conclusion: The results indicated that workplace bullying perceptions negatively affected the professional commitment levels among new graduate nurses. For the continuity of nursing human resources in the healthcare system, it is crucial to raise the awareness of health professionals, particularly nurse managers, about the transition and prevent workplace bullying through a multidimensional approach.